2014
DOI: 10.17265/2161-6264/2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Sources and Concentration on the Storage Performance of Strawberry Fruit

Abstract: Chemical application after harvest is an important method to preserve strawberry fruit quality and extend shelf life. The strawberry fruits harvested at red stage were treated with three different sources of calcium, i.e., calcium nitrate, calcium gluconate and calcium chloride at calcium concentration of 0% (distilled water), 0.5%, 1.0% and 1.5%. The strawberry fruits were dipped for 30 s. The calcium sources, calcium concentration and the interaction of calcium sources and calcium concentration significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Coating acts as a semi-permeable obstacle against carbon dioxide, oxygen, moisture and solute movement, thereby decreasing the respiration rate, water loss and alternatively oxidation reaction due to which fruit appearance is acceptable (Kumar et al, 2017) [9] . The present results are in accordance with the findings of Mahajan et al, 2009 [10] in kinnow, Akhtar and Rab, 2014 [2] in strawberry and Kumar et al, 2017 [9] in guava who observed that composite edible coated samples scored higher in sensory attributes. In winter season of 2017, fruit taste score ranged from 6.17 to 7.18 (Table 2).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Coating acts as a semi-permeable obstacle against carbon dioxide, oxygen, moisture and solute movement, thereby decreasing the respiration rate, water loss and alternatively oxidation reaction due to which fruit appearance is acceptable (Kumar et al, 2017) [9] . The present results are in accordance with the findings of Mahajan et al, 2009 [10] in kinnow, Akhtar and Rab, 2014 [2] in strawberry and Kumar et al, 2017 [9] in guava who observed that composite edible coated samples scored higher in sensory attributes. In winter season of 2017, fruit taste score ranged from 6.17 to 7.18 (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…Olive oil and Aloe vera coatings maintained taste and retained the quality of fruits during storage. The present results are supported by the findings of Marpudi et al (2011) [11] in papaya, Akhtar and Rab, 2014 [2] in strawberry and Kumar et al, 2017 [9] in guava who also observed that coated samples taste better and retained their quality during storage. The data compiled on effect of composite coatings and storage periods and their interactions on fruit total soluble solids and ascorbic acid of guava cv.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As a result, the study was set with the following five treatments: Preharvest control group cherries (sprayed with distilled water) (C1). Preharvest Ca-Glu treatment (sprayed with 1% Ca-Glu solution) (Ca1). Postharvest control group cherries (dipped into distilled water for 30 s) (C2). Postharvest Ca-Glu treatment (dipped into 1% Ca-Glu solution for 30 s) (Ca2). Pre-and postharvest Ca-Glu treatment (sprayed with and dipped into 1% Ca-Glu solution for 30 s) (Ca1 + Ca2). The doses and dipping time of Ca-Glu (Califast, Crops MCS) was chosen according to Akhtar and Rab (2014). Following each treatment, cherries were air-dried for 30 min at room conditions and packaged in plastic boxes (750 g) covered with lid having 8 perforations with 5 mm diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Tween 20 (0.1%) was added to all solutions (including control) as the spreading adhesive. The doses and dipping time of Ca-Glu (Califast, Crops MCS) was chosen according to Akhtar and Rab (2014). Following each treatment, sweet cherry fruit were air-dried for 30 min at room conditions then fruit (750 g) were placed into plastic boxes (18 cm × 11 cm × 7.5 cm).…”
Section: Methodsmentioning
confidence: 99%